THE EFFECT OF PHYSICAL SURROUNDING ON THE SATISFACTION OF SUPERMARKET IN MATARAM - A A SURYA KENCANA (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2016)
This research is aimed first at determining the effect of physical surrounding on the satisfaction of  supermarket consumers in Mataram (MGM Plaza, Niaga, Jembatan Baru and Ruby), scond at determining the physical surrounding variable that dominantly affect the supermarket consumer’s satisfaction in Mataram. This research is assosiative research to determine the correlation between two or more variable. The analysis showed that the equation regression of   Y = 0,981 + 0,078 X1 + 0,052 X2 + 0,273 X3 + 0,351 X4 . The result emphasixed the theory and researchs about the physical surrounding effect on custumer / consumers’ satisfaction. The determinanting analysis showed that R2 or R square is 0.582  the F-test = 33.058 is bigger than F-table = 2.70 wich mans the simultaneously the physical surrounding, goods pattern position  chaseer position and parking lots together affect significantly the consumers’ satisfaction. Partially, two varibles have significant variable affecting the consumers’satisfaction, namely parking lots and chaser position. Two other varable of physical surrounding and goods position do not have significant effect.